Use of 2D and multislice transperineal ultrasonography to describe the degree of perineal laceration following vaginal delivery (Medical Journal of Indonesia, 2018)
Background: Perineal tear is the most common complication after vaginal delivery. Pill-rolling test is a widely used clinical evaluation method to determine the degree of perineal tear. However, the evaluation results of anal sphincter complex (ASC) differ between clinical examination and 2D/multislice transperineal ultrasonography (TPUS). This study aims to describe measurement variation between these modalities.Methods: This cross-sectional study was conducted at Cipto Mangunkusumo Hospital from November 2015 to May 2016. Subjects were primiparous women after vaginal delivery. Clinical examination using pill-rolling test was performed to determine the degree of perineal laceration. Suture was conducted accordingly. The subjects were subjected to 2D/multislice TPUS 72 hours after delivery to evaluate the integrity of internal and external anal sphincters. Data were collected and analyzed to determine compatibility between these examinations.Results: Among 70 prospective primiparous women, five were excluded due to unavailability to undergo 2D/multislice TPUS 72 hours after delivery. The mean duration to perform 2D/multislice TPUS was 4.5 minutes, and pain was tolerable during the examination. The compatibility values of clinical examination with 2D and multislice TPUS were 0.98 and 0.93, respectively, with Cohenâs kappa of 0.92 (95% CI 0.81-1.00) and 0.79 (95% CI 0.58-0.99), respectively. Conclusion: Clinical examination is compatible with 2D/multislice TPUS for determining the degree of perineal tear after vaginal delivery.